Dexmedetomidine as an Ambulatory Sedation Agent for Abdominal MRI in Patients with Suspected Pheochromocytoma - Iradat, Prataganta; Vitraludyono, Rudy; Yupono, Karmini (Journal of Anaesthesia and Pain, 2024)
Background: Pheochromocytoma is a vascular tumor of chromaffin tissue, most commonly at the adrenal medulla, that produces and secretes norepinephrine and epinephrine and is a tumor that secretes catecholamines. Magnetic resonance imaging (MRI) is often used to provide clinical data and remains challenging in pediatrics. We present anesthesia management for abdominal MRI in pediatric patients with suspected pheochromocytoma.Case: A 12-year-old child weighing 25 kg with a diagnosis of suspected pheochromocytoma will have an abdominal MRI for diagnosis with sedation. Intravenous sedation technique using dexmedetomidine loading dose 50 μg for 10 minutes and continued maintenance of dexmedetomidine dose 17.5 μg/hour. Durante's MRI showed stable hemodynamics. Post-MRI of the abdomen, monitoring, and evaluation were carried out in the conscious recovery room and found no complications.Conclusion: The use of dexmedetomidine as a sedation agent in patients with suspected pheochromocytoma generally shows stable hemodynamics in the absence of signs of catecholamine spikes.